Unraveling the Mystery of Rathke's Cleft Cyst Presenting with Hyponatremia: A Case Report with a Comprehensive Review of Literature - Huda, Shayan; Singha, Souvik; Haidous, Ali; Bukberg, Phillip R.; Pramanik, Bidyut K.; Harshan, Manju; Mora, Luis Medina; Devita, Maria; McKeown, Amy; Boockvar, John A. (Asian Journal of Neurosurgery, 2024)
Rathke's cleft cyst (RCC) is a benign cystic lesion that is commonly discovered incidentally and remains asymptomatic in most cases. However, its association with the syndrome of inappropriate antidiuretic hormone (SIADH) secretion leading to hyponatremia (HN) is rare and has only been sporadically reported in the medical literature. In this article, we present a unique case of RCC manifesting with HN and discuss the diagnostic and management challenges encountered in a neurosurgical context. Additionally, we provide a comprehensive review of existing literature on RCC presenting with HN to enhance our understanding of this rare presentation. A 56-year-old woman with acute-onset blurry vision, headaches, and low fluid intake was diagnosed with euvolemic HN secondary to SIADH. Further evaluation revealed an intrasellar cystic lesion consistent with RCC, which was successfully resected through endoscopic transnasal transsphenoidal surgery, resulting in a complete recovery without the need for hormone replacement. The most likely explanation for the HN due to SIADH in this case is the release of accumulated antidiuretic hormone (ADH) due to compression by the cyst and the irritating effect of inflammation at this location. Accurate evaluation and classification of HN are essential for proper diagnosis and management, considering the rarity of RCC presenting with HN. A multidisciplinary approach to treatment can lead to favorable functional outcomes; however, further research is necessary to better comprehend this unique clinical entity and optimize neurosurgical approaches.
Keywords: syndrome of inappropriate antidiuretic hormone secretion; Rathke's cleft cyst; hyponatremia; hypothalamic–pituitary axis; sellar–suprasellar lesion